A preliminary report on settlement layout and gold melting at Thula Mela, a Late Iron Age site in the Kruger National Park - M.M. Kusel (Koedoe: African Protected Area Conservation and Science, 1992)
Archaeological investigations at a Late Iron Age stone-walled hill site, Thula Mela, near the Luvuvhu River in the Pafuri area of the Kruger National Park, have produced evidence of gold melting. The recovery of two fragments of pottery crucibles with the remains of slag and gold globules and three gold beads from a test trench in a midden at Thula Mela represents the first direct evidence of indigenous gold melting in South Africa. From radiocarbon dates it was established that this site was occupied between the fifteenth and early seventeenth century AD.